Crosstalk improvement of a thermo-optic polymer waveguide MZI-MMI switch - Al-Hetar, Abdulaziz M. (Elsevier, 2008)
A 2 Ã— 2 MZI-MMI switch based on thermo-optic effect with a ridge in the silicon substrate was proposed and the performance of switch was simulated. The main purpose behind this change in substrate layer is to localize the heating at a heated arm single mode waveguide and limit the increasing temperature at a second one. The switch performance of the device should be improved, compare to the usual one. Using finite difference beam propagation method (FD-BPM) and thermal computing simulation based on finite element method (FEM), the results clearly indicate that the MZI-MMI switch can satisfy -31 dB crosstalk at two states.